Broadening Perspectives on Achieving Social Change. (September 2015) - Stroebe, Katherine; Wang, Katie; Wright, Stephen C.; Stroebe, Katherine; de Lemus, Soledad
<x xml:space="preserve">Abstract</x> The articles in this special issue challenge readers to reconsider the relationships among individual mobility, collective action, and social change. Taken together, they reveal an increasing and broadening interest in the concept of social change and raise important questions about its societal applications. In this commentary, we expand on this rich body of research by considering how surface indicators of (lack of) social change such as individual versus collective action may be related to a wider range of motives than has been assumed. Moreover, we consider more carefully what constitutes social change, and discuss different forms of equality as a means to conceptualizing social change. In doing so, we attempt to move beyond implied dichotomies between individual and collective strategies and actions to consider alternative perspectives on classifying and studying social change.